Brucella Endocarditis as a Late Onset Complication of Brucellosis - Panagiotis Andriopoulos; Christos Antoniou; Panagiota Manolakou; Athanassios Vasilopoulos; George Assimakopoulos; Maria Tsironi (Case Reports in Infectious Diseases)
Brucella endocarditis (BE) is a rare but life threatening complication of brucellosis. We present a case report of a patient with relapsing brucellosis complicated with aortic valve endocarditis. The patient underwent valve replacement and required prolonged antibiotic treatment because of rupture of the noncoronary leaflet and development of congestive heart failure. Since the onset of endocarditis in patients with brucellosis is not known, proper follow-up is required in order to identify any late onset complications, especially in endemic areas.